DETERMINATION OF ORGANOCHLORINE PESTICIDE RESIDUES IN SOME VEGETABLES AND FRUIT BY QuEChERS TECHNIQUES AND GAS CHROMATOGRAPHY /MASS SPECTROMETRY - Suleiman, F.; Nuhu, A. A.; Omoniyi, K. I.; Yashim, Z. I. (FUDMA JOURNAL OF SCIENCES, 2020)
The concentrations of organochlorine pesticide residues were analysed in some vegetables and fruit (spinach, lettuce, cabbage, tomatoes, carrots and onions)  grown at Dagachi farming areas along River Galma of Zaria in Kaduna State, Nigeria. Sample collection and preparation were carried out using standard procedures. The concentrations of all the pesticides in the fruits and vegetables samples were analysed using quick easy cheap effective rugged and safe (QuEChERS) multi- residue extraction and clean up techniques, followed by gas chromatography â€“ mass spectrometry (GC â€“ MS). The most commonly detected organochlorine pesticide residues in the entire samples analysed are lindane, delta â€“ BHC, heptachlor epoxide (B), endosulfan I, dieldrin, and endosulfan II. Furthermore, the results of the study shows that the mean concentration of these organochlorines pesticide detected were higher in onion and spinach with heptachlor epoxide (B) having concentrations 2.303 mg/kg and 2.011 mg/kg respectively. Likewise, endosulfan II (1.433 mg/kg) in lettuce was observed. Heptachlor epoxide (B) detected were also very high in other samples such as carrot, cabbage, and tomatoes and with values 0.600 mg/kg, 0.716 mg/kg, and 0.524 mg/kg respectively. Indeed, these concentrations of all the organochlorine pesticides detected in the fruit and vegetables samples analysed were observed to be at alarming levels, much higher than the maximum residue limits (MRLs) by the Codex 2009 (WHO and FAO) except for lindane with values 0.007 mg/kg and 0.01 mg/kg in carrot and onions respectively
Keywords: organochlorines; pesticide; pesticide residues; vegetables; fruits; GC-MS